Improving management support tools for reintroducing bivalve species (Eastern oyster [Crassostrea virginica Gmelin]) in urban estuaries. (October 2014) - Ravit, Beth; Cooper, Keith; Buckley, Brian; Comi, Meredith; McCandlish, Elizabeth
ABSTRACT Successful reintroduction of "ecologically extinct" bivalve species into anthropogenically impaired urban estuaries is problematic when employing existing management tools used in estuaries where bivalves are present (GIS‐based restoration models, expanding existing shellfish beds, placement of shell substrate, physical oceanographic parameters). A significant management challenge is appropriate site selection. We are proposing the inclusion of a biological parameter (evaluation of tissue histopathology) in an inexpensive and rapid site selection model to inform management decision making and identify sites with the greatest potential for reintroduction success. Use of biological biomarkers is not a new concept, but it is important that they be included in a multitiered management approach to bivalve reintroduction. This Case Study tested adult Eastern Oysters (Crassostrea virginica Gmelin) from locations that supported comparable short‐term survival rates by evaluating growth and tissue health and/or disease. Biomarkers indicated oyster tissues at one site were normal, the female:male sex ratio was 50:50, and female oysters were in spawning condition. Conversely, oyster tissues at the second site exhibited multiple abnormalities, samples were 100% male, and the incidence of disease was high. Using the biomarker tool, we evaluated 4 additional sites where oysters exhibited short‐term (1 year) survival. At 2 locations, we observed chronic health impacts that would preclude reintroduction, including samples from one site where a wild population was surviving. We also analyzed tissue and shell heavy metal contents. Soft tissue metal concentrations in Meadowlands samples were at the high range of scientific literature values, averaging 1.1% of total body weight, whereas tissue metal concentrations at the Keyport site were within acceptable ranges. Although initial survival and growth rates at both locations were comparable, site‐specific urban stressors reduced oyster fitness at 1 of the 2 locations. We are proposing an Estuarine Reintroduction Site Selection Model, which includes a biological in situ parameter, to increase the probability of successfully managing a sustainable oyster reintroduction before commencing expensive large‐scale restoration activities. Integr Environ Assess Manag 2014;10:555–565. © 2014 SETAC